Managing Regional Economic Development through Local Content Requirements in Oil and Gas Industry - Semykina, Irina Olegovna (Economy of Regions, 2017)
This paper explores the regional economic impact of mineral resource endowment and offers specific inputs to the debate on the local content requirement (LCR) policy, gaining urgency in modern economic and political environment. The paper considers the intricacies related to greenfield investment projects in Russian oil and gas industry. Focusing on the experience of the Krasnoyarsk region, the paper examines the way national companies operate in the newly developing oil and gas provinces of Russia. The analysis of key economic indices shows that the existing approach does not allow having significant benefits from resource endowment in the region. The main idea is that the establishment of completely new industry has to affect regional economic development, budget revenues dynamics and employment to influence the related industries and services in the region. The conducted analysis let to form possible scenarios and evaluate the dynamics of regional economic development depending on the scale of LCR policy. The developed approach based on statistical modeling allows assessing both direct and indirect effects of LCR policy. The obtained results allow to conclude that the implementation of LCR policy leads to the growth of real income per capita and the job creation in the region. The development of equipment and services suppliers for oil and gas industry by ripple effects can boost socio-economic development and diversify regional economy. The paper also dwells on some pitfalls and risks accompanying LCR policy and considers crucial points of introducing this kind of policy for local and federal government.